Faktor – Faktor Yang Berpengaruh Terhadap Pengambilan Keputusan Pemilihan Tempat Bersalin Di Puskesmas Libarek Kabupaten Jayawijaya - Trisnawati, Endang; Mogan, Martina; Sipapa, Linda (Journal of Midwifery Science: Basic and Applied Research, 2024)
Inappropriate choice of birthing place and birth attendant will have a direct impact on the mother's health. The most ideal place for giving birth is a health facility with equipment and health workers who are ready to help at any time if birth complications occur or require emergency treatment. The aim of this research is to determine the factors that influence decision making in choosing a place to give birth at the Libarek Health Center, Jayawijaya Regency in 2023.This type of research is quantitative research with a cross sectional approach. The population in this study was all mothers giving birth normally during 2022, namely 51 respondents and domiciled in the work area of the Libarek Health Center, Jayawijaya Regency. The samples in this study were 34 samples taken using purposive sampling technique. The statistical test used is Chi-square.The research results obtained factors that influence the choice of delivery location. For the factors of knowledge, family support and access (distance to location of health facility), the p-values were respectively 0.003, 0.01 and 0.035, which means that the factors knowledge, family support and access (distance to location of health facility) influence the choice of delivery location.Conclusion: knowledge, family support and access (distance to health facilities) are factors that influence the choice of delivery place at the Libarek Health Center, Jayawijaya Regency. Keywords: Delivery place, knowledge, family support, access